Risk Factors and Outcome of Acute Kidney Injury in Children with Diabetic Ketoacidosis (Bangladesh Journal of Child Health, 2024)
Background: Children with diabetic ketoacidosis (DKA) suffer from several complications. Among them acute kidney injury (AKI) is one of the grave complications.Objectives: To determine the risk factors for development of AKI in children (age